124k views
5 votes
Please help me!!!!!!!!!!!!!!!!!

Please help me!!!!!!!!!!!!!!!!!-example-1
User Nam Vo
by
4.6k points

1 Answer

4 votes

Answer:

3x -4y -6 = 0

Explanation:

One of the ways the equation can be written is ...

(y2 -y1)(x -x1) -(x2 -x1)(y -y1) = 0

(3 -(-3))(x -(-2)) -(6 -(-2))(y -(-3)) = 0

6(x+2) -8(y +3) = 0

6x +12 -8y -24 = 0

Factoring out a common factor of 2, we get the general form equation for the line:

3x -4y -6 = 0

_____

This can be rearranged to give other forms:

3x -4y = 6 . . . . standard form

y = 3/4x -3/2 . . . . slope-intercept form

y +3 = 3/4(x +2) . . . . point-slope form

User Loren Ramly
by
5.2k points